On a Property of Concave Functions - Stigum, B. P. (Review of Economic Studies, 1968)
Journal Article On a Property of Concave Functions Get access B. P. Stigum B. P. Stigum Northwestern University, Evanston, Illinois Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 4, October 1968, Pages 413–416, https://doi.org/10.2307/2296768 Published: 01 October 1968